1971
DOI: 10.1103/physrevb.3.2698
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Upconversion in YF3:Yb3+,

Abstract: The stepwise conversion of infrared (=0.97 p) radiation to near infrared {0. 81 p) and visible (0.475 p) light in YF3 sensitized with Yb ' and activated with Tm ' has been studied in detail. The lifetimes and fluorescence intensities of the important manifolds (Yb I"&~2, Tm 3H4, Tm E4, and Tm G4), as we11 as the Yb-to-Tm transfer probability coefficients for the three steps of the process, have been measured as functions of concentration. A saturation effect previously observed in the Tm emission versus infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 11 publications
1
38
0
1
Order By: Relevance
“…The population dynamics and the emission of the different Yb 3þ and Tm 3þ levels in macroscopically sized YF 3 crystals have been described in a classical paper by Ostermayer et al 27 Nevertheless, it was demonstrated that while the first up-conversion step can be accurately characterized, the quantitative evaluation of the second and third ones is not so straightforward. 27,32 Considering all these facts, we will focus our attention in the quantification of the first energy transfer step probability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The population dynamics and the emission of the different Yb 3þ and Tm 3þ levels in macroscopically sized YF 3 crystals have been described in a classical paper by Ostermayer et al 27 Nevertheless, it was demonstrated that while the first up-conversion step can be accurately characterized, the quantitative evaluation of the second and third ones is not so straightforward. 27,32 Considering all these facts, we will focus our attention in the quantification of the first energy transfer step probability.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, in the inset of Figure 2 co-doped materials, the different energy levels of Tm 3þ ions are populated through a chain of at least three consecutive energy transfer processes from Yb 3þ ions. 27,28 These processes are schematically depicted in Figure 2(c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These transitions need to be selectively and individually excited 71,116,117 . A specific rate equations model is then proposed and its parameters adjusted to fit the experimental data.…”
Section: Numerical Solutions Of the Rate Equationsmentioning
confidence: 99%